Validation of the Airway–Dyspnoea–Voice–Swallow (ADVS) scale and Patient‐Reported Outcome Measure (PROM) as disease‐specific instruments in paediatric laryngotracheal stenosis. (8th September 2016) - Nouraei, S.A.R.; Makmur, E.; Dias, A.; Butler, C.R.; Nandi, R.; Elliott, M.J.; Hewitt, R.
Abstract : Objective: To validate the Airway–Dyspnoea–Voice–Swallow (ADVS) instrument as a disease‐specific Patient‐Reported Outcome Measure in paediatric laryngotracheal stenosis. Design: Prospective observational study. Setting: A quaternary referral centre for complex airway disease. Participants: Forty‐eight patients (30 males) with a mean age of 49 ± 49 months who underwent laryngotracheal surgery or microlaryngoscopy and bronchoscopy (MLB) following laryngotracheal surgery. Main outcome measures: Airway–Dyspnoea–Voice–Swallow summary scale and Patient‐Reported Outcome Measure (PROM), Paediatric Quality of Life (PedsQL) scale, Paediatric Voice Handicap Index (pVHI) and Lansky performance scale were administered to patients before and 6–8 weeks following airway examination/surgery. Results: Most patients (73%) had intubation‐related subglottic stenosis, and 60% of patients had prior airway treatments. The majority of patients (77%) had more than one major chronic morbidity, and the commonest procedures were diagnostic MLB (49%), followed by airway dilation (29%). Cronbach‐ α value for the ADVS PROM was 0.71 overall and 0.85, 0.86 and 0.64 for the dyspnoea, voice and swallow domains, respectively. Rank correlations between Dyspnoea, Voice and Swallow summary scale and PROM scores were 0.83, 0.71 and 0.81, respectively ( P < 0.0001). For those patients undergoing diagnostic MLB, pre‐ and post‐examination scores were highly correlated (intraclass correlations >0.75). There was a significant rank correlation between ADVS PROM score and Lansky performance score ( r = −0.68; P < 0.0001). There were significant correlations between PROM score and PedsQL ( r = −0.57; P < 0.0001) and between voice domain of the PROM and pVHI ( r = 0.78; P < 0.0001). There were strong correlations between Myer–Cotton stenosis severity and dyspnoea scale and PROM score ( r = 0.68; P < 0.0001). There were significant differences in voice and swallow ADVS scales and PROM scores between patients with and without concomitant laryngeal/oesophageal pathology. Patient age and presence of high dyspnoea and swallowing PROM scores were independently associated with poorer quality of life and performance status. Conclusions: These series of observations validate the ADVS instrument as a disease‐specific outcome measure for paediatric laryngotracheal stenosis. Dyspnoea and swallowing dysfunction appear to have the greatest impact on quality of life. More widespread adoption of the ADVS instrument could help create a shared language for outcomes communication and benchmarking for children with this complex condition.